Glucocorticoid-Induced Bone Loss Is Associated with Abnormal Intravertebral Areal Bone Mineral Density Distribution - Manning, Louise; Briggs, Andrew; Van Doornum, Sharon; Kale, Ashwini; Kantor, Susan; Wark, John (Hindawi Publishing Corporation, 2013)
Individuals with glucocorticoid-induced osteoporosis experience vertebral fractures at an increased rate and at higher vertebral areal bone mineral density (aBMD) than individuals with primary osteoporosis. Standard posteroanterior- (PA-) projection dual energy X-ray absorptiometry (DXA) lacks the diagnostic sensitivity required for reliable estimation of vertebral fracture risk in individuals. Assessment of subregional vertebral aBMD using lateral-projection DXA may improve the predictive value of DXA parameters for fracture. One hundred and four individuals were recruited and grouped for this study: primary osteoporosis with no history of vertebral fracture (n = 43), glucocorticoid-induced bone loss (n = 13), and healthy controls (n = 48). Standard PA-projection and supine-lateral scans were performed, and lateral scans were analysed according to an established protocol to measure aBMD within 6 subregions. Main effects for subregion and group were assessed and observed, by ANCOVA. Ratios were calculated between subregions and compared between groups, to overcome the potentially confounding influence of variability in subregional geometry. Significantly lower values were observed in the glucocorticoid group for the ratios of (i) anterior subregion: whole vertebral body and (ii) posterior: whole vertebral body when compared to the primary osteoporosis and control groups (P < 0.0 5). Lower anterior subregional aBMD in individuals on glucocorticoid therapy may help to explain the increased vertebral fracture risk in this patient group.